Welfare developmentalism with interactive central–local relations: Understanding the recent expansion in pension coverage in China. (16th August 2022) - Guo, Yu; Zhao, Liqiu
Abstract: This study presents an analytical framework integrating welfare developmentalism and interactive central–local relations to understand the underlying dynamics of the dramatic pension coverage expansion in China in the last decade. We empirically test the research hypotheses based on the analytical framework using data from the Chinese General Social Survey 2008–2017. The results show that various individual and institutional factors, including demographic profiles, socio‐economic status, institutional contexts, and regional economic development, are significant predictors of pension participation. Regions with more local capacity have higher pension participation rates; however, there has been a trend towards regional convergence in China's pension coverage expansion since 2012. This study contributes to the literature on the social policymaking process by revealing how the forces of top‐down pressure from the centre and bottom‐up motivations derived from the local conditions are embedded into the conceptual framework of welfare developmentalism. Our findings imply that the implementation of an inclusive pension scheme requires careful policy design and coordination among regions to address the interests of different parties.